Analysis of pooled real-world data from Germany, Italy, and the United States of rVIII-SingleChain compared with standard- and long-acting FVIII products for prophylaxis of hemophilia A. (3rd July 2022) - Olivieri, Martin; Simpson, Mindy; Yan, Songkai; Fedorovsky, Johanna; Zhang, Xiang; Tomic, Radovan; Pinachyan, Karen; Mancuso, Maria Elisa
Abstract: Objective: To evaluate real-world annualized bleeding rates (ABRs), dosing frequency, and factor consumption of four recombinant FVIII (rFVIII) products using pooled data from centers in the US, Germany, and Italy. Methods: De-identified patient medical chart data were collected from 48 hemophilia treatment centers in the US, Germany, and Italy. Patients included in this analysis had hemophilia A and were treated with rVIII-SingleChain, rFVIIIFc, octocog alfa, or BAY 81-8973 for ≥12 weeks. Where possible, patient selection considered age and disease severity in order to balance patient groups across products. Summary statistics were presented descriptively by product for dosing frequency, consumption, ABR/annualized spontaneous bleeding rate (AsBR), and corresponding percentage of patients with zero bleeds. Logistic regression was performed for patients with zero bleeds or zero spontaneous bleeds (vs. patients with any such bleeds). Generalized linear model regression was performed for ABR, AsBR, and consumption. All regression models included the product variable for comparison as well as additional independent variables for adjustment (age, weight, severity, and country for the consumption model, with the addition of consumption for the bleeding outcomes models). Results: Overall, 616 patients were included (rVIII-SingleChain, n  = 129; rFVIIIFc, n  = 159; octocog alfa, n  = 181; BAY 81-8973, n  = 147). Dosing frequency was ≤2 times a week for 65.9%, 75.5%, 25.4%, and 40.1% of patients treated with rVIII-SingleChain, rFVIIIFc, octocog alfa, and BAY 81-8973, respectively. ABRs were not significantly different among products, with mean (median) values of 1.1 (0.0), 1.0 (0.0), 1.4 (1.0), and 1.9 (1.0) for rVIII-SingleChain, rFVIIIFc, octocog alfa, and BAY 81-8973, respectively. The percentage of patients with zero bleeds was comparable between rVIII-SingleChain and rFVIIIFc (59.7% vs. 62.3%; p  =.916) and significantly higher for rVIII-SingleChain compared with octocog alfa ( p  <.001) and BAY 81-8973 ( p  =.003). Comparison of mean weekly consumption showed: rVIII-SingleChain (83.0 IU/kg/week) vs. rFVIIIFc (96.9; p  =.055) and significantly lower for rVIII-SingleChain vs. octocog alfa (108.6; p  <.001) and BAY 81-8973 (104.3; p  =.001). The median values for weekly consumption were 85.7, 90.1, 100.1, and 98.5 IU/kg/week for rVIII-SingleChain, rFVIIIFc, octocog alfa, and BAY 91-8973, respectively. Similar trends were observed for all outcomes when analyzing the subgroups of patients aged ≥12 years and patients with severe disease (all age and ≥12 years). Conclusions: rVIII-SingleChain prophylaxis may provide improved bleed protection, less frequent dosing, and lower consumption compared with standard-acting FVIII products, and comparable protection and consumption to the other long-acting FVIII product, in patients with hemophilia A.